Stephen Coonts' Deep Black - Coonts, Stephen 1946- and DeFelice, Jim 1956- (New York St. Martin's Paperbacks, 2003)
When a spy plane gathering information on a new Russian weapon is shot down by a mysterious MiG, Deep Black, the covert operations team of the National Security Agency, is sent in to uncover the truth about the incident, as former Marine sniper Charlie Dean and ex-Delta Force trooper Lia DeFrancesca stumble upon a plot to assassinate the Russian president and overthrow the government.
Keywords: Intelligence Officers -- National security -- Cyberterrorism